Effects of skeletal element identity, delipidation and demineralization on the analysis of stable isotope ratios of C and N in fish bone. Issue 2 (12th December 2017) - Bas, M.; Cardona, L.
Abstract : Stable isotope ratios of C and N in the bone tissue of three different skeletal elements (angular, cleithrum and vertebra) of three fish species from different evolutionary lineages (Clupeiformes, Atheriniformes and Notothenioidei) were determined before (δ 13 Cbulk and δ 15 Nbulk ) and after demineralization and delipidation (δ 13 Cdml and δ 15 Ndml ). One of the species had cellular bone and the other two had acellular bone. Results revealed that δ 15 N and δ 13 C values from different skeletal elements were interchangeable in species with acellular bone, but caution was needed in species with cellular bone, as δ 15 N values varied among skeletal elements. Furthermore, δ 15 Nbulk values were significantly lower than δ 15 Ndml values in the three species, thus suggesting that they are not comparable. This difference is probably because δ 15 Nbulk refers to total bone protein and δ 15 Ndml to collagen only.